1992
DOI: 10.1021/ja00040a013
|View full text |Cite
|
Sign up to set email alerts
|

The enantioselective synthesis of (-)-physostigmine via chiral sulfoxides

Abstract: Recovered 46b (0.66 g, 1.3 1 mmol) was dissolved in CH2C12 (1 3 mL), cooled down to -70 'C, and treated with gaseous BF, (165 mL, 6.5 mmol). The mixture was kept at this temperature for 20 min and then quenched with MeOH (absolute, 2 mL). After the usual treatment the mixture 46a,b was isolated (0.56 g, yield ca. 85%, a:b = 3:1) and identified by 'H NMR data comparison of the decomplexed material with the abovementioned sample.Acknowledgment. Abstract:The total synthesis of naturally occurring (-)-physostigmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…They reported that the size of the alkyl group on the sulfoxide positively correlates with the degree of asymmetric induction. [190] Lactonization of isopropyl indolyl sulfoxide 164, followed by desulfonylation and dechlorination, gave 165 (in good enantiomeric excess), which was then transformed into (À)-2 (Scheme 33).…”
Section: A C H T U N G T R E N N U N G [33]-sigmatropic Rearrangemenmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the size of the alkyl group on the sulfoxide positively correlates with the degree of asymmetric induction. [190] Lactonization of isopropyl indolyl sulfoxide 164, followed by desulfonylation and dechlorination, gave 165 (in good enantiomeric excess), which was then transformed into (À)-2 (Scheme 33).…”
Section: A C H T U N G T R E N N U N G [33]-sigmatropic Rearrangemenmentioning
confidence: 99%
“…Enantioselective synthesis of (À)-physostigmine (2). [190] a) Zn/CuCl, Cl 3 CCOCl, THF, 0 8C; b) nBu 3 SnH, AIBN, toluene, reflux, 37 % (2 steps), 70-75 % ee; c) HCO 2 H, then MeCO 2 CHO, 94 %; d) MeNH 2 , À30 8C to RT, then H 2 SO 4 cat., DMF, 115 8C, 68 %; e) BH 3 ·THF, 0 8C to reflux, 64 %; f) Ni-Raney (W2), THF, reflux; g) Na cat., MeNCO, 60 % (2 steps). AIBN = azobisisobutyronitrile; Scheme 34.…”
Section: A C H T U N G T R E N N U N G [33]-sigmatropic Rearrangemenmentioning
confidence: 99%
“…We tentatively assign this as the (P) configuration shown because (+)- [5]-helicene has the (P) configuration (3 1 …”
Section: Me0mentioning
confidence: 98%
“…For background to physostigmine and related marine natural products, see: Marino et al (1989Marino et al ( , 1992. For recent, related structural and synthetic studies, see: Pozza Silveira et al (2012); Silveira & Marino (2013).…”
Section: Related Literaturementioning
confidence: 99%